Upaya Peningkatan Kualitas Manajerial Lembaga Pendidikan Islam Melalui TQM - Mulyadi, Mulyadi (ZAHRA: Research and Tought Elementary School of Islam Journal, 2020)
ABSTRACT One of the important challenges of Islamic educational institutions today is the weak managerial quality of the institution. This article will discuss Total Quality Management (TQM) in educational institutions, how to improve the quality of educational institutions that are managed. TQM is a management approach that can be applied in Islamic education institutions to be more effective in managing their educational resources. TQM is also called integrated quality management because it departs from efforts to improve quality in an integrated manner, covering quality, energy, infrastructure, management, and graduates.